1987
DOI: 10.1063/1.452801
|View full text |Cite
|
Sign up to set email alerts
|

Crystallization and glass formation processes in liquid sodium: A molecular dynamics study

Abstract: Glass formation and crystallization of liquid and glass rubidium: A constantpressure moleculardynamics study Defects and fluorine diffusion in sodium fluoroberyllate glass: A molecular dynamics study J. Chem. Phys. 75, 3516 (1981); 10.1063/1.442461 ESR and Mössbauer studies of crystallization process of sodium iron silicate glass Crystallization and glass formation processes are studied for the sodium system with 108 atoms by means of molecular dynamics simulation with constant volume. The equilibrium liquids,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
0

Year Published

1990
1990
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 17 publications
1
20
0
Order By: Relevance
“…MD can provide important insight by allowing one to determine quantities which are difficult to access in real experiments and hard to obtain with reasonable precision [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…MD can provide important insight by allowing one to determine quantities which are difficult to access in real experiments and hard to obtain with reasonable precision [25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40].…”
Section: Introductionmentioning
confidence: 99%
“…The difference in cohesive energy (^0.01%) appears to be too small, however, to provide a basis for an explanation of an observed preference for one of the two structures in molecular-dynamics (MD) simulations of crystallization in the supercooled LJ liquid. In fact, until very recently, such a preference has never been found [2][3][4][5][6][7], suggesting the inadequacy of the LJ potential to model the interatomic interactions in a simulation of either fee or hep crystal growth.It is the purpose of this Letter to investigate the role that lattice defects may play in the simulated crystallization process, and, in particular, to demonstrate that growth-stimulating defects are much more probable to occur in fee crystallites than in hep crystallites. Moreover, it will be shown that such defects exclusively stimulate fee growth, without further assumptions regarding the interatomic potential other than that it is isotropic and short ranged.…”
mentioning
confidence: 99%
“…The difference in cohesive energy (^0.01%) appears to be too small, however, to provide a basis for an explanation of an observed preference for one of the two structures in molecular-dynamics (MD) simulations of crystallization in the supercooled LJ liquid. In fact, until very recently, such a preference has never been found [2][3][4][5][6][7], suggesting the inadequacy of the LJ potential to model the interatomic interactions in a simulation of either fee or hep crystal growth.…”
mentioning
confidence: 99%
“…Among these are studies on pure metals, such as sodium, 7 potassium, 8 rubidium, 9 nickel, 10 and iron, 11 and binary metal-alloys including good glass formers like Ni-Zr, 12,13 Ti-Al, 14 and Ni 33 Y 67 . 15 In this paper, we use molecular dynamics in conjunction with the quantum Sutton-Chen ͑Q-SC͒ force fields ͑FF͒, [16][17][18] to examine melting and quenching of CuNi and CuAg alloys.…”
Section: Introductionmentioning
confidence: 99%